2017
DOI: 10.1038/s41598-017-10215-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive transcriptome profiling of Salvia miltiorrhiza for discovery of genes associated with the biosynthesis of tanshinones and phenolic acids

Abstract: Tanshinones and phenolic acids are crucial bioactive compounds biosynthesized in Salvia miltiorrhiza. Methyl jasmonate (MeJA) is an effective elicitor to enhance the production of phenolic acids and tanshinones simultaneously, while yeast extract (YE) is used as a biotic elicitor that only induce tanshinones accumulation. However, little was known about the different molecular mechanism. To identify the downstream and regulatory genes involved in tanshinone and phenolic acid biosynthesis, we conducted comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 53 publications
5
72
0
Order By: Relevance
“…While in S. miltiorrhiza , exogenous MeJA treatment can promote the accumulation of tanshinone (Gu et al, 2012; Kai et al, 2012; Hao et al, 2015). In our study, we noticed that SmWRKY1 can be induced by exogenous MeJA treatment, reaching a maximal level at 0.5 h after MeJA treatment., which is consistent with the previous reports that MeJA treatment could increase tanshione production (Hao et al, 2015; Zhou et al, 2017). Recent studies showed that Brassica napus WRKY33 (BnWRKY33), a S. sclerotiorum-responsive gene, could positively regulate resistance to S. sclerotiorum by enhancing the expression of genes involved in camalexin synthesis and genes regulated by salicylic acid (SA) and jasmonic acid (JA) (Liu et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…While in S. miltiorrhiza , exogenous MeJA treatment can promote the accumulation of tanshinone (Gu et al, 2012; Kai et al, 2012; Hao et al, 2015). In our study, we noticed that SmWRKY1 can be induced by exogenous MeJA treatment, reaching a maximal level at 0.5 h after MeJA treatment., which is consistent with the previous reports that MeJA treatment could increase tanshione production (Hao et al, 2015; Zhou et al, 2017). Recent studies showed that Brassica napus WRKY33 (BnWRKY33), a S. sclerotiorum-responsive gene, could positively regulate resistance to S. sclerotiorum by enhancing the expression of genes involved in camalexin synthesis and genes regulated by salicylic acid (SA) and jasmonic acid (JA) (Liu et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…Extraction and qualitative analysis of phenolic acids in S. miltiorrhiza hairy root followed the methods described by Zhou et al (2017) with minor modification. Briefly, the hairy root was dried until a constant weight was obtained, grounded into powder and sieved through a 0.45 mm screen.…”
Section: Methodsmentioning
confidence: 99%
“…), and gases (oxygen, carbon dioxide, ethylene, etc.). In the studies of Salvia miltiorrhiza hairy roots, it was found that JA, SA, Ag + , and yeast extract can enhance the production of tanshinones in hairy roots .…”
Section: Application Of Elicitors In the Ginsenoside Biosynthesismentioning
confidence: 99%